Beneficial effects of a combination of natural product activators of autophagy on endothelial cells and platelets. (24th April 2021) - Carnevale, Roberto; Nocella, Cristina; Schiavon, Sonia; Cammisotto, Vittoria; Cotugno, Maria; Forte, Maurizio; Valenti, Valentina; Marchitti, Simona; Vecchio, Daniele; Biondi Zoccai, Giuseppe; Rubattu, Speranza; Martinelli, Ombretta; et al.
Abstract : Background and Purpose: Oxidative stress and insufficient autophagy activity are associated with inflammatory processes and are common features of many cardiovascular diseases (CVDs). We investigated if a combination of natural activators of autophagy could modulate oxidative stress, platelet aggregation and endothelial cell survival and function in response to stress. Experimental Approach: Ex vivo platelet aggregation and activation, H2 O2 production and autophagy were measured in platelets of subjects at high cardiovascular risk, including smokers, patients with metabolic syndrome (MetS) and patients with atrial fibrillation (AF). In vitro, the effects of a mixture of natural pro‐autophagy molecules and antioxidants on platelets and human umbilical vein endothelial cells (HUVECs) were evaluated. Key Result: Autophagy appeared to be inhibited, whereas aggregation was increased in platelets from AF and MetS patients and in smokers, as compared with healthy subjects. Treatment of platelets isolated from these patients with a mixture composed of trehalose, spermidine, catechin and epicatechin (Mix1) or with a mixture composed of trehalose, spermidine and nicotinamide (Mix2), significantly reduced platelet activation and oxidative stress, and increased autophagy, compared with the effect of each compound alone. Similarly, treatment of HUVECs with a combination of these compounds exhibited beneficial effects and increased endothelial cell survival, nitric oxide bioavailability and angiogenesis in response to stress in a potentiated manner. Conclusion and Implications: A combination of natural activators of autophagy could inhibit platelet activity and oxidative stress and improve endothelial cell survival and function in a potentiated manner representing a useful strategy to reduce the effect of risk factors on CVD occurrence. LINKED ARTICLES: This article is part of a themed issue on Cellular metabolism and diseases. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v178.10/issuetoc